Determinant Factors in Stock Returns of Food and Beverage Industry Companies in Indonesia - Rohman, Muhammad Amin Fatkur; Saefudin (Journal of Management Studies and Development, 2024)
This study aims to analyze the influence of internal and external factors on stock returns in destroying the food and beverage industry listed on the IDX from 2011 to 2021. The sample in this study used a purposive sampling technique or was based on specific criteria with 12 companies. This research data is panel data, namely a combination of times series and cross-section data, which is tested statistically using Stata. Three data analyses are used: model estimation test, model selection, and static panel regression model estimation results with the criterion of a P value < 0.05, so there is a significant influence between the independent and dependent variables. The research results prove that the best model chosen is the CEM model. The research results demonstrated that the variables ROE (P Value: 0.543 > 0.05), DER (P Value: 0.491 > 0.05), interest rates (P Value: 0.373 > 0.05), and inflation (P Value: 0.165 > 0.05) statistically does not affect stock returns. However, the exchange rate variable (P Value: 0.005 < 0.05) significantly impacts stock returns. The research results also prove that ROE, DER, interest rates, exchange rates, and inflation can explain stock returns of 12.30%. In comparison, the remaining 87.70% is influenced by other variables not included in the research.